Continental Calvinian influences on the Scottish Reformation: The first book of discipline (1560) - Whytock, Jack C. (Hors série, 2009)
Foreword / by P.J. Buys -- Introduction -- Theme and importance -- Nature : historical and theological -- Usage of the word "reformed" -- The Scottish Reformation -- Influences upon The first book of discipline -- Calvin on discipline, a theological perspective -- Relationships of basic dependence -- Calvin on discipline -- The nature of the church : invisible yet visible -- The identification of the visible church -- The church as our mother -- The holy bride for God's glory -- Common discipline -- Clergy discipline -- The purpose of discipline -- The authority for discipline -- John à Lasco and his influence on The first book of discipline -- Historical connections between à Lasco and the Scottish reformers -- John Willock -- John Knox -- À Lasco's writings and The first book of discipline : a comparison -- Superintendents -- The prophesying -- Discipline proper -- Valérand Poullain and his influence on The first book of discipline -- Historical connections between Poullain and the Scottish reformers -- John Willock -- John Knox -- Poullain's work and The first book of discipline : a comparison -- The election of ministers -- Elders -- Discipline proper -- The French reformed church and The first book of discipline -- Historical connections between the French Reformed Church and the Scottish reformers -- John Knox -- Other Scottish reformers -- La discipline ecclesiastique and The first book of discipline : a comparison -- Ministerial election and discipline -- The office of elder -- Discipline proper -- Excursus -- Calvinian sixteenth century discipline